If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 24 = 10x + -20 Reorder the terms: 24 + 6x = 10x + -20 Reorder the terms: 24 + 6x = -20 + 10x Solving 24 + 6x = -20 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 24 + 6x + -10x = -20 + 10x + -10x Combine like terms: 6x + -10x = -4x 24 + -4x = -20 + 10x + -10x Combine like terms: 10x + -10x = 0 24 + -4x = -20 + 0 24 + -4x = -20 Add '-24' to each side of the equation. 24 + -24 + -4x = -20 + -24 Combine like terms: 24 + -24 = 0 0 + -4x = -20 + -24 -4x = -20 + -24 Combine like terms: -20 + -24 = -44 -4x = -44 Divide each side by '-4'. x = 11 Simplifying x = 11
| 6x^2-18x+0=0 | | C=2(8)-2 | | 2(3x+2)=4x+16 | | 5w-6-2w=18 | | 12b-6+2-3b=4b+5 | | 3/8x-1/4 | | m+7=-37 | | 2/3(9-21/2)=2 | | 26=x+x+2x-2 | | 2n^2+15n=0 | | m+7=37 | | 7x+6=13x-6 | | 7/9x+2/3=19x | | 5n+3=14-6m | | x+7=40+4x | | (5v-7)(v+2)=0 | | 2/3(6x-7)=2 | | 44=4x | | m+7=29 | | 24-6x=y | | 85=5(-5a-3) | | 9x+10=-x+13 | | -6(3x+7)=-18x-42 | | 4m-13=6-3(1-4m) | | 2=4(3y-8)-11y | | 5x+5=9-(5x-5) | | 1/6x12 | | 5m-6-3m= | | 12x^2-19x-18=0 | | 5/12=11/3m-6 | | 9/x=13 | | 3a+9=-3a+5 |